Enhanced thermoelectric performance of SnTe: High efficient cation - anion Co-doping, hierarchical microstructure and electro-acoustic decoupling. (May 2018) - Zhou, Zhiwei; Yang, Junyou; Jiang, Qinghui; Lin, Xuesong; Xin, Jiwu; Basit, Abdul; Hou, Jingdi; Sun, Bingyang
Abstract: In this work, the co-doping in both the anion and cation sites of SnTe has been implemented by addition of BiCl3 and the effect of co-doping on thermoelectric performance of SnTe-based materials has been studied detailedly. Benefitting from the sharp reduction of carrier concentration and the increase of density of states due to the electron donor contribution of Bi and Cl, the electrical transport properties have been improved greatly; moreover, the hierarchical architectures such as the point defects, dislocations, nano-particles and phase/grain boundaries act as multiscale phonon scattering centers and effectively suppress the transport of phonons in wide frequency range, thus reduced the thermal conductivity dramatically. Due to the synergistic regulation of cation-anion co-doping, a maximum ZT of 1.27 at 873 K has been obtained in the sample of SnTe doping with 4% BiCl3, which enhances by 182% in comparison with the pristine sample. Graphical abstract: fx1 Highlights: Doping with multiple heteroatoms in both the cation and anion positions. A one-step synergistic regulation of the electrical and thermal transport properties of SnTe. The electro-acoustic decoupling arised from high efficient co-doping and their supersaturated precipitation.